2012
DOI: 10.1016/j.bios.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Surface plasmon resonance-biosensor detects the diversity of responses against epidermal growth factor in various carcinoma cell lines

Abstract: Surface plasmon resonance (SPR) biosensor detects intracellular signaling events as a change of the angle of resonance (AR). We previously reported that the activation of epidermal growth factor receptor (EGFR) on keratinocytes causes a unique triphasic change of AR, whereas the activation of other receptors, such as IgE receptor and adenosine A3 receptor on mast cells, causes a transient monophasic increase of AR. To study the mechanism of AR changes induced by EGFR activation, we introduced wild and mutated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 16 publications
(22 reference statements)
3
16
0
Order By: Relevance
“…Next, solutions containing stimuli are flowed over the cells, and their response is measured in real time by SPR. This strategy has been successfully applied to detect and diagnose malignant tumors cells, such as Chinese hamster ovary cells without the use of immunological labels [ 86 ]. Liu et al designed an SPR biosensing system with anti-VEGF antibodies immobilized on the surface and living SKOV-3 ovarian cancer cells cultured on the flow cell chamber ceiling [ 87 ].…”
Section: Applications Of Spr-based Biosensorsmentioning
confidence: 99%
“…Next, solutions containing stimuli are flowed over the cells, and their response is measured in real time by SPR. This strategy has been successfully applied to detect and diagnose malignant tumors cells, such as Chinese hamster ovary cells without the use of immunological labels [ 86 ]. Liu et al designed an SPR biosensing system with anti-VEGF antibodies immobilized on the surface and living SKOV-3 ovarian cancer cells cultured on the flow cell chamber ceiling [ 87 ].…”
Section: Applications Of Spr-based Biosensorsmentioning
confidence: 99%
“…Chen et al demonstrated that GPCR-mediated SPR responses in CHO cells were induced by density changes on the sensor chip surface [15]. Finally, the inhibition of receptor activities by molecular engineering totally abolished SPR signals, preserving the binding activities of ligands [14,16,17]. These observations demonstrate that RI near the plasma membrane, which might reflect accumulation and rearrangement of proteins activated by intracellular signal transduction, dramatically changes in response to exogenous stimuli.…”
Section: Cell Reactions/molecules Detection By Sprmentioning
confidence: 99%
“…Surface plasmon resonance (SPR) is a powerful analytical technology. It can detect the thickness of the films absorbed onto the sensor surface and interactions between biomolecules such as antigen-antibody or protein-DNA [1][2][3][4][5]. In comparison with traditional detection methods, like X-ray, HPLC, and HPLC-MS, SPR technology can perform kinetics parameters (association and dissociation process) measurement, concentration measurement, and real-time molecule detection.…”
Section: Introductionmentioning
confidence: 99%